Artikel Riview: Profil Studi Fitokimia Dan Aktivitas Farmakologi Buah Mangga (Mangifera Indica L.) - Kurrota Ayyun; Rosydah, Yeka Khafidz Ila; Atikah, Nandiyyah; Arianti, Shabrina Putri; Maulidini, Cici; Agustino, Faizal; Putri, Nadiya Kamiliya; Seran, Agustinus Alfred; S.Klau, Ivan Charles; Ningsih, Arista Wahyu (CV. ITTC INDONESIA, 2023)
The mango plant (Mangifera indica L.) is a plant that is often found around. Empirically, this plant has been widely used in traditional medicine around the world, one of which is ayuverda treatment from India. Due to these many empirical functions, many studies have been conducted on the pharmacological activities of mango plants. This article discusses the pharmacological activities and phytochemical tests that have been investigated and confirmed both in vitro and in vivo with the literature review method. The results obtained show the presence of several compounds found in mango plants such as: alkaloids, flavonoids, terpenoids, saponins, tannins, phenols and steroids. Because of the compounds contained in mango plants, there are several pharmacological activities including: antioxidant activity, antidiabetic, anti-inflammatory, hepatoprotective, anti-hyperlipidemia, anti-hyperglycemia, antimicrobial, antiobesity, antifungal, antidiarrheal, and antitumor, among others.